Effect of the defect densities of reduced graphene oxide network on the stability of lithium-metal anodes. (June 2021) - Zhang, Huan; Huang, Meiling; Song, Jie; Sun, Daming; Qiao, Yingjun; Zhou, Xuemei; Ye, Changying; Liu, Wenping; Liu, Wenjing; Wei, Zhikai; Peng, Gongchang; Qu, Meizhen
Abstract: Graphene is considered an ideal lithium metal host material to suppress dendrite growth and buffer volume changes. Although defects on graphene are generally considered to enhance its lithiophilicity, defects that promote unstable solid electrolyte interphase (SEI) growth are rarely noticed. To explore which defect density of graphene is the most ideal host material, different defect densities of graphene are prepared as Li-metal host materials through thermal reduction at different temperatures (200 °C, 400 °C, 800 °C, 1200 °C, 1600 °C and 2200 °C). We are the first to demonstrate that molten lithium can spread into a graphene matrix with any density of defects and that Li2 C2 is formed in less-defective 2200 °C rGO/Li anode. The 2200 °C rGO/Li composite anode exhibits the best electrochemical performance in all rGO/Li anodes, and the symmetrical cell with 2200 °C rGO/Li electrode shows stable cycling for 1200 h with a small polarization voltage of 12 mV at 1 mA cm −2 . Moreover, the 2200 °C rGO/Li || S full cell displays stable cycling performance even with a high sulfur loading of 9.4 mg cm −2 ; additionally, a high initial areal capacity of 9.7 mA h cm −2 can be realized.